2022
DOI: 10.3390/scipharm90040059
|View full text |Cite
|
Sign up to set email alerts
|

Potential and Alternative Bioactive Compounds from Brown Agaricus bisporus Mushroom Extracts for Xerosis Treatment

Abstract: This study aimed to investigate the ability of brown Agaricus bisporus extracts to enhance xerosis treatment via their biological activities, including their antioxidant, anti-aging, and anti-inflammation. Brown A. bisporus ethanol extract (EE) and brown A. bisporus water extract (WE) contained ergothioneine and gallic acid as their major compounds, as detected by HPLC, respectively. The WE exhibited the highest total polysaccharide content (734.04 ± 0.03 mg glucose/g extract) and total phenolic content (190.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…Since collagenase is the enzyme that is capable of degrading collagen, which is a major component of the extracellular matrix that plays key functions in skin tightening and skin resilience, inhibiting this enzyme would lead to a delay in the aging process associated with the skin [ 111 , 112 ]. Collagen fibers have usually been thought of as the main fibrillar component of the skin’s dermis layer, a layer of connective tissue between the outermost skin layer (the epidermis) and the deepest skin layer (the subcutaneous fat layer).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since collagenase is the enzyme that is capable of degrading collagen, which is a major component of the extracellular matrix that plays key functions in skin tightening and skin resilience, inhibiting this enzyme would lead to a delay in the aging process associated with the skin [ 111 , 112 ]. Collagen fibers have usually been thought of as the main fibrillar component of the skin’s dermis layer, a layer of connective tissue between the outermost skin layer (the epidermis) and the deepest skin layer (the subcutaneous fat layer).…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, the excessive production of the collagenase enzyme was shown to cause dry skin in adults older than 60 years. This can lead to severe xerosis, which is marked by skin inflammation, itching, and fissured and cracked skin [ 112 ]. As a result, the inhibition of collagenase, along with the stabilization of damaging free radicals, is crucial for the prevention of cell damage.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the four species under analysis, the ethanolic extract of A. bisporus demonstrated the most significant capacity to inhibit the enzyme hyaluronidase at 1 and 10 mg DE/mL, with values reaching 43.0 ± 7.1% and 74.4 ± 7.5%, respectively, and an IC 50 of 5.4 ± 0.4 mg DE/mL. Recently, Nitthikan et al [58] also assessed the hyaluronidase inhibitory activity of brown A. bisporus extracts. The authors found that, at 1 mg/mL, the ethanolic and the aqueous extracts inhibited the hyaluronidase enzyme by 55.03 ± 0.25 and 55.94 ± 3.98%, respectively.…”
Section: Cosmeceutical Properties Of Mushroom Extractsmentioning
confidence: 93%
“…The inhibition of collagenase (COLInh) was calculated using Equation (2): where A 0 is the absorbance of the negative control (water), and A s is the absorbance of the respective extract. Gallic acid was used as the positive control [ 26 , 27 ]. COLIC 50 values (μL extract/mL) were calculated as the concentration of the extract that inhibited 50% of collagenase activity.…”
Section: Methodsmentioning
confidence: 99%